2022
DOI: 10.3389/fonc.2022.1087778
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant chemotherapy and survival outcomes in rectal cancer patients with good response (ypT0-2N0) after neoadjuvant chemoradiotherapy and surgery: A retrospective nationwide analysis

Abstract: BackgroundFor rectal cancer, it remains unclear how to incorporate tumor response to neoadjuvant chemoradiotherapy (nCRT) when deciding whether to give adjuvant chemotherapy. In this study, we aim to determinate the survival benefit of adjuvant chemotherapy for rectal cancer patients with good response (ypT0-2N0) after nCRT and surgery.MethodsThe study cohort included 720 rectal cancer patients who had good response (ypT0-2N0) after nCRT and surgery, who did or did not receive adjuvant chemotherapy between Jan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…A total of 29 [ 15 19 , 26 , 28 31 , 33 52 ]. studies, including 9 [ 18 , 26 , 29 , 31 , 35 , 38 , 39 , 43 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 29 [ 15 19 , 26 , 28 31 , 33 52 ]. studies, including 9 [ 18 , 26 , 29 , 31 , 35 , 38 , 39 , 43 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…For the pooled analysis, we only included the most recently published studies from this database. Given the 18 [ 16 , 17 , 19 , 28 , 30 , 33 , 34 , 36 , 37 , 40 42 , 44 46 , 50 52 ]. studies with reporting on the effect of ACT on the hazard ratio of OS in patients with rectal cancer in pCR, the pooled analysis showed that ACT improved overall survival (HR = 0.803, 95% CI 0.678–0.952, P = 0.011) without any observed heterogeneity ( I 2 = 0%, χ 2 = 14.66, P = 0.620) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations